A brief description of the Andromeda Zn-Cu prospect in the Albany-Fraser Orogenic belt: A geophysical discovery using HT SQUID. Issue 1 (1st December 2019) - Polito, Paul; Crawford, Tony; Worthington, Tim; Whitford, Mike; Sheppard, Somealy
Summary: The Andromeda Zn-Cu-Au-Ag prospect is a geophysical discovery that represents the first VMS prospect of significance in the Albany-Fraser Orogenic belt, Western Australia. The prospect was first identified following a ground Transient Moving Loop Electromagnetic survey over a structural ellipse that is recognised in aeromagnetic data and has similarities to the Nova "eye". A conductive plate, 450 m from surface was drilled, but it was the subsequent Down Hole Transient Electromagnetic survey that ultimately led to the intersection of 29.9 m @ 2.5% Zn, 1.4% Cu from 548 m and confirmed the discovery. Andromeda is classified as a strongly deformed Besshistyle, VMS deposit that has been metamorphosed at low granulite grade conditions. Ore lenses reach 20 m true width and comprise coarse‐grained pyrrhotite, pyrite, sphalerite and chalcopyrite. This paper outlines the geophysical methods used to identify and discover Andromeda and describes our current understanding of the geology, mineralogy and representative geochemistry.